Integrating persons with disabilities into Mongolia society. (Observations and suggestions., 2019)
In Mongolia, persons with disabilities still face significant challenges in their daily lives despite the adoption of progressive legislation on their rights. More needs to be done in the country to facilitate their societal integration and meet the aims of the Convention of the Rights of Persons with Disabilities of the United Nations. Suggested reforms aim for a better understanding and assessment of disabilities to facilitate developments for better access to infrastructure, transport, and information as well as inclusive education and employment.